The 'Giraffe': discovery of a stripped red giant in an interacting binary with an ∼2 M⊙ lower giant. Issue 4 (6th August 2022) - Jayasinghe, T; Thompson, Todd A; Kochanek, C S; Stanek, K Z; Rowan, D M; Martin, D V; El-Badry, Kareem; Vallely, P J; Hinkle, J T; Huber, D; Isaacson, H; Tayar, J; et al.
ABSTRACT: We report the discovery of a stripped giant + lower giant Algol-type binary, 2M04123153+6738486 (2M0412), identified during a search for non-interacting compact object – star binaries. 2M0412 is an evolved ( T eff, giant ≃ 4000 K), luminous ( L giant ≃ 150 L⊙ ) red giant in a circular P = 81.2 d binary. 2M0412 is a known variable star previously classified as a semiregular variable. The cross-correlation functions of follow-up Keck/HIRES and LBT/Potsdam Echelle Polarimetric and Spectroscopic Instrument (PEPSI) spectra show an radial velocity variable second component with implied mass ratio q = M giant / M comp ≃ 0.20 ± 0.01. The All-Sky Automated Survey for SuperNovae (ASAS-SN), Asteroid Terrestrial-impact Last Alert System (ATLAS), Transiting Exoplanet Survey Telescope ( TESS ), and Zwicky Transient Facility (ZTF) light curves show that the giant is a Roche lobe filling ellipsoidal variable with an inclination of 49.4 ± 0.3°, and a giant mass of M giant = 0.38 ± 0.01 M⊙ for a distance of ≃ 3.7 kpc. The mass of the giant indicates that its envelope has been partially stripped. The giant companion on the lower red giant branch has a mass of M comp = 1.91 ± 0.03 M⊙ with T eff, comp ≃ 5000 K, L comp ≃ 60 L⊙, and R comp ≃ 11 R⊙ . The lower giant contributes ${\sim }35{{\ \rm per\ cent}}$ of the flux in the V band. We also identify an orbital phase dependent, broad $\rm H\, α$ emission line which could indicate ongoing accretion from the stripped red giant on to the companion.